Characterization of outcomes and practices utilized in the management of internal carotid artery injury not requiring definitive endovascular management. Issue 4 (17th July 2021) - London, Nyall R.; AlQahtani, Abdulaziz; Barbosa, Siani; Castelnuovo, Paolo; Locatelli, Davide; Stamm, Aldo; Cohen‐Gadol, Aaron A.; Elbosraty, Hussam; Casiano, Roy; Morcos, Jacques; Pasquini, Ernesto; Frank, Georgio; et al.
Abstract: Background: After internal carotid artery (ICA) injury during endoscopic skull base surgery, the majority of patients undergo ICA embolization or stenting to treat active extravasation or pseudoaneurysm development. However, management practices when embolization or stenting is not required have not been well described. The objective of this study was to determine how patients with ICA injury but no embolization, stenting, or ligation do long‐term and ascertain the reconstruction methods utilized. Methods: Twenty‐nine cases of ICA injury were identified in an international multi‐institutional retrospective review. Of these, we identified six cases that were not treated with embolization, stenting, or ICA sacrifice. Information was available for five cases. Results: A muscle patch was used in the immediate repair of each case. A nasoseptal flap was used in one case. Prefabricated nasal tampons were used in all cases. Nasal packing was initially left in for a median of 7 days prior to removal. The initial muscle patch was reinforced with a second muscle graft in one case. One case demonstrated ICA bleeding at the time of packing removal and was repacked an additional week. Follow‐up for each of these cases was at least 2 years. No cases of subsequent carotid rupture were found and none of these cases ultimately underwent endovascular stenting. Radiation or proton therapy has not been subsequently used in any of these patients. Conclusions: This study details the reconstruction, lessons learned, and long‐term follow‐up for five cases of ICA injury not treated with embolization, stenting, or ligation.